Expected Money Growth, Markov Trends and the Instability of Money Demand in the Euro Area - Sylvia Kaufmann; Peter Kugler (Oesterreichische Nationalbank (OeNB), 2006)
This paper analyzes the recently documented instability of money demand in the euro area in the framework of a Markov switching trend model. First, we consider a standard flexible price model with stable money demand, rational expectations, and an exogenous income-money ratio which follows a Markov trend. This framework, which implies an influence of expected future money on prices, leads to a cointegrating relationship between (log) prices and the (log of the) money-income ratio with a switching intercept term. Of course, this likely leads to a rejection of cointegration by standard tests and to the erroneous conclusion of an unstable money demand. Second, a more general model allowing for endogeneity and more general dynamics is estimated with Bayesian methods for euro area data from 1975-2003. This exercise provides support for our model and a stable demand for M3 in the euro area.
Keywords: C11; C32; E41; 330; Bayesian cointegration analysis; Markov trend; Markov chain Monte Carlo; money demand